The genealogy and history are grey (Revista de História Regional, 2008)
The critical ones of Nietzsche against History did not aim at discipline it accurately and yes the historians who, for it, cultivated a senile and declining history. By the way, he was as soon as it understood the science of its century. History would have to surpass the illness of the eighteenth man becoming a mix of sorts, namely, critic, traditional and monumental.